E-leadership, an unavoidable challenge for today's organizations (2016)
The aim of this study is to describe and conceptualize the notion of electronic leadership, and the challenge that entail for the leaders the new ways of relationship that this kind leadership involves. The complexity to lead virtual teams is analyzed from a bibliographic review, considering the new communication forms, different from traditional ones, that the leaders have to face, suggesting changes in leadership styles, so that organizations can leverage the advantages of technology and avoid being relegated to an increasingly virtualized world. Finally, the limitations and possibilities to develop a suitable leadership for virtual environments are discussed in order to advance in this emergent field of knowledge. © 2016 Universidad ICESI. Published by Elsevier España, S.L.U. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).